America's Original Sin : Racism, White Privilege, and the Bridge to a New America - Wallis, Jim (Grand Rapids : Brazos Press, 2016)
America's problem with race has deep roots, with the country's foundation tied to the near extermination of one race of people and the enslavement of another. Racism is truly our nation's original sin. "It's time we right this unacceptable wrong," says bestselling author and leading Christian activist Jim Wallis. Fifty years ago, Wallis was driven away from his faith by a white church that considered dealing with racism to be taboo. His participation in the civil rights movement brought him back when he discovered a faith that commands racial justice. Yet as recent tragedies confirm, we continue to suffer from the legacy of racism. The old patterns of white privilege are colliding with the changing demographics of a diverse nation. The church has been slow to respond, and Sunday morning is still the most segregated hour of the week. In America's Original Sin, Wallis offers a prophetic and deeply personal call to action in overcoming the racism so ingrained in American society. He speaks candidly to Christians -- particularly white Christians -- urging them to cross a new bridge toward racial justice and healing. Whenever divided cultures and gridlocked power structures fail to end systemic sin, faith communities can help lead the way to grassroots change. Probing yet positive, biblically rooted yet highly practical, this book shows people of faith how they can work together to overcome the embedded racism in America, galvanizing a movement to cross the bridge to a multiracial church and a new America.
Fifty years ago Wallis was driven away from his faith by a white church that considered dealing with racism to be taboo. His participation in the civil rights movement brought him back when he discovered a faith that commands racial justice. He shows that, as a nation, we continue to suffer from the legacy of racism, and the church has been slow to respond. Here he offers a deeply personal call to action in overcoming the racism so ingrained in American society.
Introduction: You will know the truth, and the truth will set you free -- Race is a story -- The parables of Ferguson and Baltimore -- The original sin and its legacy -- Repentance means more than just saying you're sorry -- Dying to whiteness -- A segregated church or a beloved community? -- From warriors to guardians -- The new Jim Crow and restorative justice -- Welcoming the stranger -- Crossing the bridge to a new America.
Includes bibliographical references and index.
Keywords: United States -- Race relations; Racism -- United States